Catheter-Directed Thrombolysis for Submassive Pulmonary Embolism - Chiarello, Matthew A.; Sista, Akhilesh K. (Seminars in Interventional Radiology, 2018)
Acute pulmonary embolism (PE) is a leading cause of morbidity and mortality in the United States. PE associated with right ventricular strain, termed submassive or intermediate-risk PE, is associated with an increased rate of clinical deterioration and short-term mortality. Trials have demonstrated systemic thrombolytics may improve patient outcomes, but they carry a risk of major hemorrhage. Catheter-directed thrombolysis (CDT) may offer similar efficacy to and a lower risk of catastrophic hemorrhage than systemic thrombolysis. Three prospective trials have evaluated CDT for submassive PE; ULTIMA, SEATTLE II, and PERFECT. These trials provide evidence that CDT may improve radiographic efficacy endpoints in submassive PE with acceptable rates of major hemorrhage. However, the lack of clinical endpoints, long-term follow-up, and adequate sample size limit their generalizability. Future trials should be adequately powered and controlled so that the short- and long-term effectiveness and safety of CDT can be definitively determined.
Keywords: Catheter-Directed Thrombolysis; submassive pulmonary embolism; ultrasound-assisted thrombolysis; interventional radiology